2012
DOI: 10.1177/0165025412444643
|View full text |Cite
|
Sign up to set email alerts
|

Differences in agency? How adolescents from 18 countries perceive and cope with their futures

Abstract: This study investigated how N ¼ 5,126 adolescents (mean age of 15 years) from 18 countries perceive and cope with future-and schoolrelated stress. The adolescents completed the Problem Questionnaire (PQ), which assesses stress, and the Coping Across Situations Questionnaire (CASQ), which assesses three coping styles (reflection/support-seeking, emotional outlet, and withdrawal/denial). Across countries, adolescents reported considerably higher levels of future-related stress than school-related stress. The ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 57 publications
(98 reference statements)
2
33
0
2
Order By: Relevance
“…Eppelmann and colleagues [ 54 ] demonstrated that stress could prompt behavioural and emotional difficulties and result in an association of stress and emotional and behavioural problems partly mediated by withdrawal from parents. Furthermore, parental pressure could influence medical students’ school performance and result in academic stress [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eppelmann and colleagues [ 54 ] demonstrated that stress could prompt behavioural and emotional difficulties and result in an association of stress and emotional and behavioural problems partly mediated by withdrawal from parents. Furthermore, parental pressure could influence medical students’ school performance and result in academic stress [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A sample item is "I found it difficult to discover what profession really suits me." The PQ has been used frequently across countries with good reliability (e.g., Seiffge-Krenke et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Senior and junior researchers from all seven countries translated the Perceived Parental Behavior Scale into the official language of each country and then back into English. As stated above, the YASR, PQ, and CASQ had already been translated and used in previous cross-cultural studies (Persike & Seiffge-Krenke, 2016;Seiffge-Krenke et al, 2012). Further, the AIDA (Goth, Foelsch, Schlüter-Müller, & Schmeck, 2016) and the DIDS (Morsünbül & Ç ok, 2014) have been used in several cross-cultural samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents also face the challenges of learning to live independently and building their own social network by exploring and building their identities and starting romantic relationships (Steinberg and Morris 2001). At the same time, many adolescents experience stress in relation to school (e.g., Salmela-Aro et al 2009; Seiffge-Krenke et al 2012). Ninth-grade adolescents, who formed the target group of this study and who are finalizing their compulsory education, also face new personal and academic challenges because, for example, they have to complete a great deal of school projects and have to clarify their interests to be able to choose their future educational path.…”
Section: Introductionmentioning
confidence: 99%